2017
DOI: 10.3389/feart.2017.00006
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Cycles of Meltwater Percolation, Refreezing, and Drainage in the Supraglacial Snowpack of Haig Glacier, Canadian Rocky Mountains

Abstract: Meltwater refreezing and storage in the supraglacial snowpack can reduce and delay meltwater runoff from glaciers. These are well-established processes in polar environments, but the importance of meltwater refreezing and the efficiency of meltwater drainage are uncertain on temperate alpine glaciers. To examine these processes and quantify their importance on a mid-latitude mountain glacier, we measured the temperature and meltwater content in the upper 50 cm of the supraglacial snowpack of Haig Glacier in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(63 citation statements)
references
References 52 publications
(96 reference statements)
2
61
0
Order By: Relevance
“…Early in the ablation season, the entire depth of liquid water within the snowpack can refreeze overnight (Mätzler and Hüppi, 1989). Later in the season, the bulk of the snowpack more often remains wet with a thin layer of refreeze just at the surface, typically in the first 10 centimeters; in this case, the snowpack remains ripe but the refrozen crust presents an energy deficit that must be overcome before melt can resume the next day (Macelloni et al, 2005;Samimi and Marshall, 2017). The "recycling" of melt water due to nightly refreeze can act as a significant energy sink.…”
Section: Diurnal Fluctuations In Energy Balancementioning
confidence: 99%
See 3 more Smart Citations
“…Early in the ablation season, the entire depth of liquid water within the snowpack can refreeze overnight (Mätzler and Hüppi, 1989). Later in the season, the bulk of the snowpack more often remains wet with a thin layer of refreeze just at the surface, typically in the first 10 centimeters; in this case, the snowpack remains ripe but the refrozen crust presents an energy deficit that must be overcome before melt can resume the next day (Macelloni et al, 2005;Samimi and Marshall, 2017). The "recycling" of melt water due to nightly refreeze can act as a significant energy sink.…”
Section: Diurnal Fluctuations In Energy Balancementioning
confidence: 99%
“…The "recycling" of melt water due to nightly refreeze can act as a significant energy sink. For example, Samimi and Marshall (2017) concluded that 10-15% of available melt energy for a given season was diverted to warm and melt refrozen meltwater on the Haig Glacier in Canada.…”
Section: Diurnal Fluctuations In Energy Balancementioning
confidence: 99%
See 2 more Smart Citations
“…Measurement of capillary pressure using 10 porous cup tensiometers was described by Colbeck (1976) and Wankiewics and De Vries (1978), although more recent use is not widely reported. Measurement of water saturation in snow has been accomplished using dielectric methods (Denoth, 1989) and time domain reflectometry (TDR) (Diaz et al, 2017, andSamimi andMarshall, 2017). The use of electrical methods is emerging as a possible approach to measure flux in percolating meltwater.…”
Section: Introduction 20mentioning
confidence: 99%